2011
DOI: 10.1007/s10439-011-0431-1
|View full text |Cite
|
Sign up to set email alerts
|

On the Use of In Vivo Measured Flow Rates as Boundary Conditions for Image-Based Hemodynamic Models of the Human Aorta: Implications for Indicators of Abnormal Flow

Abstract: The purpose of this study is to investigate how the imposition of personalized, non-invasively measured blood flow rates as boundary conditions (BCs) influences image-based computational hemodynamic studies in the human aorta. We extracted from 4D phase-contrast MRI acquisitions of a healthy human (1) the geometry of the thoracic aorta with supra-aortic arteries and (2) flow rate waveforms at all boundaries. Flow simulations were carried out, and the implications that the imposition of different BC schemes bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
105
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 147 publications
(113 citation statements)
references
References 45 publications
7
105
1
Order By: Relevance
“…54 In addition, the flow rate ratio and waveform at each supra-aortic artery would further affect the flow transport in the aorta. 32 …”
Section: Helical Flow In Human Vasculaturementioning
confidence: 97%
“…54 In addition, the flow rate ratio and waveform at each supra-aortic artery would further affect the flow transport in the aorta. 32 …”
Section: Helical Flow In Human Vasculaturementioning
confidence: 97%
“…adopted emphasizes that the PC-MRI flow measurements-derived uncertainty is an important source of uncertainty. This is of utmost importance considering that it is non-linearly related with other uncertainties intrinsic in modeling assumptions such as aortic wall distensibility (Lantz et al 2011;Brown et al 2012), outflow boundary conditions (Gallo et al 2012), blood rheological properties (Liu et al 2011), etc. As a consequence, the global effect cannot be neglected when looking at model reliability.…”
Section: Discussionmentioning
confidence: 99%
“…The MRI data sequence was extensively detailed in several previous studies (Morbiducci et al 2009;Morbiducci et al 2011a;Tresoldi et al 2014;Volonghi et al 2016), and reported in other computational hemodynamics studies (Gallo et al 2012;Morbiducci et al 2013Morbiducci et al , 2015. Briefly, 4D MRI images of an ostensibly healthy human aorta were acquired using a 1.5 T scanner (Achieva, Philips Healthcare, The Netherlands).…”
Section: Pc-mri Datamentioning
confidence: 99%
See 1 more Smart Citation
“…1a was applied. As a first step, from the in vivo 4D dataset (2 9 2 mm 2 , slice thickness equal to 4 mm, slice spacing equal to 2 mm spatial resolution; 38 ms temporal resolution), the geometrical model of the thoracic aorta was built and the flow rate waveforms, applied as conditions at boundaries of the vascular model, were extracted as in ref [8] (Fig. 2).…”
Section: Methodsmentioning
confidence: 99%